Analysis of digestive tract content of the larvae of Polybia scutellaris (White) (Hymenoptera, Vespidae) - Fernández Corujo, Victoria Lilian (2011)
Fil: Fernández Corujo, Victoria Lilian. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.